Stopping Powers and Inelastic Mean Free Path of 100 eV to 30 keV Electrons in Zirconium Silicates - D. Tahir; Suarga Suarga; Yulianti Yulianti; N.H. Sari (Atom Indonesia, 2012)
We have determined the electron stopping power (SP) and inelastic mean free path (IMFP) of (ZrO2)x(SiO2)1-x (x=1, 0.75, 0.5, 0.25, 0) for electron energies from 100 eV to 30 keV by means of modified Born–Ochkur equations. The energy loss function (ELF) is required in the calculation of SP and IMFP. We used the electron energy losses from 0 to 80 eV obtained by quantitative analysis of reflection electron energy-loss spectroscopy (REELS) spectra. The values of SP and IMFP for high contents of ZrO2 (x=50% and x=75%) in Zr-silicates are similar to those of ZrO2, and similar to those of SiO2 for low contents of ZrO2 (x=25%) in Zr-silicates. There are small differences in the values of SP and IMFP for ZrO2 and SiO2.We found that the SP decreases while the IMFP increases with increasing electron energy. We have demonstrated that the ELF obtained from the quantitative analysis of REELS spectra provide us with a straightforward way to determine SP and IMFP for alloy materials by using modified Born-Ochkur equations. Received: 04 December 2012; Revised: 18 December 2012; Accepted: 19 December 2012